A loss-of-function AGTR1 variant in a critically-ill infant with renal tubular dysgenesis: case presentation and literature review - Aljazi Al-Maraghi (14056975) (2024)
Background Renal tubular dysgenesis (RTD) is a severe disorder with poor prognosis significantly impacting the proximal tubules of the kidney while maintaining an anatomically normal gross structure. The genetic origin of RTD, involving variants in the ACE, REN, AGT, and AGTR1 genes, affects various enzymes or receptors within the Renin angiotensin system (RAS). This condition manifests prenatally with oligohydramninos and postnatally with persistent anuria, severe refractory hypotension, and defects in skull ossification. Case presentation In this report, we describe a case of a female patient who, despite receiving multi vasopressor treatment, experienced persistent hypotension, ultimately resulting in early death at five days of age. While there was a history of parental consanguinity, no reported family history of renal disease existed. Blood samples from the parents and the remaining DNA sample of the patient underwent Whole Genome Sequencing (WGS). The genetic analysis revealed a rare homozygous loss of function variant (NM_000685.5; c.415C > T; p.Arg139*) in the Angiotensin II Receptor Type 1 (AGTR1) gene. Conclusion This case highlights the consequence of loss-of-function variants in AGTR1 gene leading to RTD, which is characterized by high mortality rate at birth or during the neonatal period. Furthermore, we provide a comprehensive review of previously reported variants in the AGTR1 gene, which is the least encountered genetic cause of RTD, along with their associated clinical features. Other Information Published in: BMC Nephrology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12882-024-03569-z